Knowledge, Attitudes, and Practices (KAP) of Communities toward Rabies Prevention in Indonesia: A Literature Review - Kale, Maria Laurenci Fanny Permata; Riwu, Audrey Gracelia; Wuhan, Yustinus Oswin Primajuni (Jurnal Veteriner Nusantara, 2025)
Rabies remains a serious zoonotic threat in Indonesia, with thousands of animal bite cases and dozens of human deaths annually. This review article aims to identify the level of community knowledge, attitudes, and practices (KAP) regarding rabies prevention in Indonesia and highlight the importance of a socio-cultural approach in supporting the national rabies elimination program. Data have been collected from scientific articles published between 2015 and 2025. Results indicate that the community’s basic knowledge about rabies is quite high, but there is still a gap between knowledge and actual practice, especially in rural and eastern Indonesia. The involvement of traditional leaders and a One Health approach is recommended to improve the effectiveness of education and compliance with rabies prevention.